(untitled) (Research, Society and Development, 2020)
Introduction: Oncological care is performed by a multiprofessional health team, composed of different specialists, who need to be prepared not only from the technical scientific point of view, but also emotionally, in order to face a tense routine of diagnosis, treatment and prognosis related to the patient diagnosed with cancer and his family. Thus, these professionals are more vulnerable to the development of Burnout syndrome. Method: In this study, an integrative literature review was carried out, aiming to understand the relationship between Burnout Syndrome and Oncological assistance provided by health professionals in this area. Results: The selected texts were subjected to thematic analysis, after being classified according to the concepts brought by each author, with five thematic axes of discussion being identified: Burnout related to work factors correlating leave for health reasons, Burnout associated with professional factors and personal, as well as the barriers encountered; and coping proposals to reduce this scenario. Conclusion: It was possible to notice that the emotional burden demanded by the care and management of cancer patients and their families, as well as all the factors involved in the process, both personal and work, have an important relationship with the appearance of the symptoms that lead to Burnout Syndrome. The selected studies reinforce the need to invest in training with the teams in order to prevent the appearance of Burnout, as well as to recognize in advance potential signs and symptoms presented by professionals that may be suggestive of the syndrome.